2021
DOI: 10.1519/ssc.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

Injury Prevention in Tennis Players, Linking the Kinetic Chain Approach With Myofascial Lines: A Narrative Review With Practical Implications

Abstract: Myofascial chains refer to the soft tissue elastic connections that envelop the muscles throughout the entire body. Evidence points to the ability of myofascial chains to transfer the force developed in one muscle-tendon-joint unit to other proximal or distal musculotendinous units. Tennis is a sport demanding repetitive high-power unilateral movements, which predisposes the players to various musculoskeletal adaptations that may interrupt their optimal biomechanics and result in possible injuries. Myofascial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…These two ideas, however, might be viewed as two sides of the same coin, according to recent studies [ 8 , 11 ]. A study by Licen et al [ 19 ] linked the KC approach with myofascial training in tennis players to maximize rehabilitation and prevention programs, which are primarily intended to reduce the incidence of injuries and positively influence biomechanical patterns of movement, muscle coordination, and muscle force production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two ideas, however, might be viewed as two sides of the same coin, according to recent studies [ 8 , 11 ]. A study by Licen et al [ 19 ] linked the KC approach with myofascial training in tennis players to maximize rehabilitation and prevention programs, which are primarily intended to reduce the incidence of injuries and positively influence biomechanical patterns of movement, muscle coordination, and muscle force production.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehending how muscle activation in various joints interacts to produce biomechanically powerful but also safe movements could enable us to use customized conditioning and rehabilitation strategies to correct poor biomechanics. Because the malfunctioning of a KC indicates a significant injury risk, it is crucial to be aware of the frequent occurrence of pain or injury caused by inefficient biomechanics that result in changed force distributions and power outputs [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the wireless motion capture system provided some assistance in training processes and pre-competition evaluations of athletes. Ličen et al [8] incorporated myofascial training into the training of tennis players with the goal of optimizing rehabilitation and prevention programs, lowering injury rates, and producing beneficial effects on the biomechanical patterns of exercise. Qu et al [9] used big data to analyze the biomechanical and kinematic indicators in table tennis training.…”
Section: Introductionmentioning
confidence: 99%
“…This article provides a slightly different perspective than most in discussing the development of a strength training program for tennis athletes. We are fully aware of the important role Olympic lifts, previously highlighted sport specific movements and multi-joint exercises can and do play in preparing tennis athletes for proper performance enhancement as well as injury prevention (Ličen, et al, 2022;Roetert et al, 2009a;Roetert et al, 2009b;Reid et al, 2007). In fact, based on the specificity principle of training, training programs should be both physiologically and mechanically specific to the demands of tennis (Colomar et al, 2023;Baiget et al, 2019;Martin & Prioux, 2011).…”
Section: Introductionmentioning
confidence: 99%